2019
DOI: 10.1111/add.14852
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of trends in wastewater‐based data and traditional epidemiological indicators of stimulant consumption in three locations

Abstract: Aims To compare long‐term trends in wastewater data with other indicators of stimulant use in three locations and to test the reliability of estimates based on 1 week of sampling. Design Comparison of trends in quantities (‘loads’) of stimulants or their metabolites in wastewater with trends in other indicators of stimulant use (e.g. treatment, police, population survey data). Setting and Participants Populations in Oslo (Norway), South‐East Queensland (Australia) and Eindhoven (the Netherlands). Measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Several examples from the literature showed different approaches and strategies to tackle the uncertainty associated with WBE studies. For example, Goulding and Hickman assumed three main sources of uncertainty (fluctuations in flow, uncertainty in analytical determinations, and the actual size of the population served by the wastewater treatment plant) and, using Bayesian statistics, fitted the data to linear regression hierarchical models (Goulding and Hickman 2020). Other modelling approaches (Croft et al 2020) considered Monte Carlo simulations to deal with uncertainties and with the propagation of errors associated with the parameters that are usually considered in WBE.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples from the literature showed different approaches and strategies to tackle the uncertainty associated with WBE studies. For example, Goulding and Hickman assumed three main sources of uncertainty (fluctuations in flow, uncertainty in analytical determinations, and the actual size of the population served by the wastewater treatment plant) and, using Bayesian statistics, fitted the data to linear regression hierarchical models (Goulding and Hickman 2020). Other modelling approaches (Croft et al 2020) considered Monte Carlo simulations to deal with uncertainties and with the propagation of errors associated with the parameters that are usually considered in WBE.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraethylene glycol is used in a wide variety of applications (e.g., personal care products, vehicle antifreeze, dispersants) and has been widely detected in the environment . However, co-occurrence of methamphetamine, a compound previously suggested as a wastewater indicator compound, in all targeted urban waters indicated that simple assessments of presence or absence of typical representative chemical indicator(s) ,, may lack sufficient resolution for tracking wastewater contributions. This observation reflected previous reports that contaminants traditionally considered “wastewater derived”, such as prescription/recreational drugs, have been frequently detected in urban receiving waters that are disconnected from known sewage sources, with elevated levels especially evident during storm events. , …”
Section: Resultsmentioning
confidence: 99%
“…In terms of interpretation, it is key to recognize that an increasing trend in volumes of a substance detected is complex and can be linked to a range of consumption and market-related factors [18, 20, 29, 32]. Importantly, there is a need to explore the factors underpinning the increase (more consumers, increased individual consumption, drug purity increases, or any combination of these).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, additional data sources will be needed for further interpretation of the findings. Observed trends may additionally be influenced by timevarying and unobserved factors, such as changes in drug purity over the observation period [2,18,[30][31][32][33]. In this respect, an observed increase in daily loads may have a negligible association with street volume/weight units, but rather the increased purity of the product on the market.…”
Section: Introductionmentioning
confidence: 99%